Beyond the screen : youth ministry for the connected but alone generation - Zirschky, Andrew (2015)
How to minister to a generation in the world of social media. It's no secret that teenagers are perpetually connected via social media and mobile devices, but while we've analyzed as a culture how youth are connecting we've done less well at understanding why teenagers are drawn to the glow of the screen. Beyond the Screen explores the reality that teenagers use these technologies in desperate bid for an intimacy and depth of relationship largely absent from face-to-face society and the church. Employing the latest ethnographic research on youth and digital media in tandem with theological reflection and interviews with teens themselves, author Andrew Zirschky provides a deeper glimpse into the world of teens and social media and gives new direction and directives for ministering to Millennials. (Publisher).
Batteries not desired: social media and the teenage search for presence -- "Taking my friends with me": life in the digital diaspora -- Presence text: why short messages mean more than you think -- The great shift: youth and the rise of networked individualism -- Digital demands: what networked individualism requires of youth -- Being communion: Corinth and the alternative operating system of koinonia -- Communities of the face: full presence in a world of partial relationships -- Whoever loses his network: beyond fear and anxiety in networked individualism -- Beyond the hidden self of the curated soul: finding friendship in communion -- From selective sociality to open embrace: practicing creative love for the abandoned -- The spirit and the screen: social media as a location for epicletic practices.
Includes bibliographical references (pages 150-160).
Keywords: Church work with youth; Youth -- Religious life; Christianity and culture; Internet -- Religious aspects -- Christianity; Information technology -- Religious aspects -- Christianity; Christianity and culture; Church work with youth; Information technology -- Religious aspects -- Christianity; Internet -- Religious aspects -- Christianity; Youth -- Religious life; Prof's picks -- 2016 -- 11 (Nov) -- Kimball